2017
DOI: 10.1021/acsami.7b14185
|View full text |Cite
|
Sign up to set email alerts
|

Detection of T4 Polynucleotide Kinase via Allosteric Aptamer Probe Platform

Abstract: As a vital enzyme in DNA phosphorylation and restoration, T4 polynucleotide kinase (T4 PNK) has aroused great interest in recent years. Therefore, numerous strategies have been established for highly sensitive detection of T4 PNK based on diverse signal amplification techniques. However, they often need sophisticated design, a variety of auxiliary reagents and enzymes, or cumbersome manipulations. We have designed a new kind of allosteric aptamer probe (AAP) consisting of streptavidin (SA) aptamer and the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Abnormal T4 PNK activity has been closely associated with several human genetic syndromes, so screening of its inhibitors is of great importance in drug development and clinical treatment. In this work, (NH 4 ) 2 SO 4 and ADP are selected as model inhibitors. (NH 4 ) 2 SO 4 can inactivate T4 PNK by changing its configuration, and ADP can interfere with the phosphate group transfer process from ATP to DNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal T4 PNK activity has been closely associated with several human genetic syndromes, so screening of its inhibitors is of great importance in drug development and clinical treatment. In this work, (NH 4 ) 2 SO 4 and ADP are selected as model inhibitors. (NH 4 ) 2 SO 4 can inactivate T4 PNK by changing its configuration, and ADP can interfere with the phosphate group transfer process from ATP to DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, excellent ECL performance in terms of stability and efficiency is achieved from the PeQDs-NCDs@HZIF-8. To illustrate the potential application of PeQDs, the ternary nanocomposite is then employed for ECL evaluation of T4 polynucleotide kinase (T4 PNK) activity, which plays a crucial role in DNA repair and cellular metabolism. In this strategy (Scheme ), we design a multifunctional DNA probe with a 5′-hydroxyl terminal, which undergoes phosphorylation of T4 PNK and cleavage of λ-exonuclease (λ-Exo) to activate the fragments for hybridization chain reaction (HCR) and electrode capture. Afterward, the HCR is triggered to generate a large amount of double-stranded DNA (dsDNA) for the assembly of rhodamine 6G (Rh6G).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, they have been widely used in several analytical techniques because of their high ability to bond specifically with target substances and their easy modification and fixation (Cruz-Aguado & Penner, 2008;Duan et al, 2012;Espiritu et al, 2018;Fenzl et al, 2017;Noonan et al, 2013). Aptamers are often used in combination with fluorescent labelling materials to achieve sensitive and intuitive detection (Gao et al, 2017;Wu et al, 2018). Currently, the most widely used fluorescent labelling materials are organic fluorescent dyes, fluorescent proteins, and quantum dot materials.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Compared with ion chromatography, 28 flow injection analysis 29 and titration analysis detection methods, 30 fluorescence method is simple, low cost and widely used. [31][32][33] In view of these and as part of our research interest in ions recognition, [34][35][36][37][38] herein, we reported a novel sensor molecule (HB1) based on 4-(diethylamino)-2-(hydroxy)-phenyl imine functionalized naphthalimide derivative (Scheme 1). Interestingly, the sensor molecule HB1 could not only fluorescence detection CNin DMSO/H 2 O (8 : 2, v/v) solution but also dual-channel (absorption and fluorescence) detection of Fe 3+ in DMSO solution with high selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%